2004
DOI: 10.1002/jqs.879
|View full text |Cite
|
Sign up to set email alerts
|

Environmental change and peatland forest dynamics in the Lake Sentarum area, West Kalimantan, Indonesia

Abstract: Four short pollen and charcoal records from sites within and around Lake Pemerak on the margins of the Danau (Lake) Sentarum National Park in inland West Kalimantan, supported by modern surface samples from the Reserve, provide a partial picture of lowland equatorial vegetation and environments over at least the last 40 000 years. They demonstrate general stability in the distribution of wetland and ombrotrophic (or raised) peatlands through the recorded period with dominance throughout of peatland and swamp f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 28 publications
2
63
0
1
Order By: Relevance
“…Selected radio Carbon ages of tropical peats in Kalimantan and Peninsular Malaysia are so variable, spanning from 30 000 to hundreds of years (Anshari et al, 2001(Anshari et al, , 2004Page et al, 2004;Wüst and Bustin, 2004;Wüst et al, 2008). The radio Carbon analysis indicates that coastal peat in the Kapuas River basin is formed around 3000-4000 years BP (see Table 2).…”
Section: Regional Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected radio Carbon ages of tropical peats in Kalimantan and Peninsular Malaysia are so variable, spanning from 30 000 to hundreds of years (Anshari et al, 2001(Anshari et al, , 2004Page et al, 2004;Wüst and Bustin, 2004;Wüst et al, 2008). The radio Carbon analysis indicates that coastal peat in the Kapuas River basin is formed around 3000-4000 years BP (see Table 2).…”
Section: Regional Settingmentioning
confidence: 99%
“…Anshari et al (2004) reported that the age of peat from Danau Sentarum National Park in the upper Kapuas River is greater than 30 000 yrs BP (see Table 3). Further, a basal radio Carbon date of peat from Sebangau National Park is 20 000 yrs BP (Page et al, 2004).…”
Section: Regional Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, model results for the region greatly vary, with some indicating that a broad continuous lowland tropical rainforest was maintained and others suggesting savanna over major portions of Sundaland during the LGM (6,7). Surprisingly, there are no records from peninsular Malaysia and, in places where LGM sediments with suitable proxies are recovered, they may be compromised by biases such as riparian gallery forest vegetation and wind-blown tree pollen dominating riverine and offshore deposits (6,8,11,12), or lowland swamp regions being biased toward indicating wetter conditions (13). Hence, even the general distribution of LGM vegetation is disputed.…”
mentioning
confidence: 99%
“…Pollen diagrams from Lake Sentarum and Setia Alam in west-central and south-central Borneo (Anshari et al, 2004;Kershaw et al, 2001) provide evidence for tropical rainforest during the Late Glacial Maximum (LGM) in those areas. It is suspected, however, that during these times dry dipterocarp woodland and savannah expanded into regions now occupied by humid lowland rainforest (Hope et al, 2004;Bird et al, 2005).…”
Section: Biogeography and Rain-forest Refugia In Ois 3 E Evidence Andmentioning
confidence: 96%